2016
DOI: 10.1080/21513732.2016.1169559
|View full text |Cite
|
Sign up to set email alerts
|

Traditional ecological knowledge on shifting cultivation and forest management in East Borneo, Indonesia

Abstract: Forest utilization of indigenous communities is intimately connected to experiences and knowledge arising from the interaction between people and their environment. The traditional ecological knowledge of the Dayak Tunjung communities in East Borneo offers an interesting example of the interrelation between agricultural food production, forest management and local culture. This study describes how the local villagers manage their rice cultivation system combined with forest succession based on traditional ecol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 11 publications
(11 reference statements)
2
34
0
2
Order By: Relevance
“…However, the study also found that awareness of and compliance with traditional norms and practices are associated more with older village residents than with younger generations. This intergenerational erosion of forestrelated traditional knowledge, revealed both in this study and in that of the Ifugao communities in the Philippines (Camacho et al 2016) and among the Dayak Tunjung in East Borneo (Siahaya et al 2016), highlights the need for greater emphasis on both conservation of traditional knowledge and appropriate adaptation of traditional practices to meet the changing livelihood needs of younger generation without losing the multiple ecosystem service benefits that traditional practices have typically yielded.…”
Section: Editorialmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the study also found that awareness of and compliance with traditional norms and practices are associated more with older village residents than with younger generations. This intergenerational erosion of forestrelated traditional knowledge, revealed both in this study and in that of the Ifugao communities in the Philippines (Camacho et al 2016) and among the Dayak Tunjung in East Borneo (Siahaya et al 2016), highlights the need for greater emphasis on both conservation of traditional knowledge and appropriate adaptation of traditional practices to meet the changing livelihood needs of younger generation without losing the multiple ecosystem service benefits that traditional practices have typically yielded.…”
Section: Editorialmentioning
confidence: 99%
“…Similarly, the study by Siahaya et al (2016) describes the traditional knowledge that has guided the development of upland rice cultivation based on sophisticated shifting cultivation techniques -gilir balikused by the indigenous Dayak Tunjung community in East Borneo, who for generations have relied on these practices to ensure their food security. A study of rural communities in northern Ghana by Boafo et al (2016) examines how traditional knowledge in its various forms -taboos and totems, customs and rituals, rules and regulations, traditional protected areas -still play an important role in managing ecosystem services in these villages.…”
Section: Editorialmentioning
confidence: 99%
See 2 more Smart Citations
“…Only participants from Buluq Sen recognized the importance of Supporting Service (e.g., soil fertility). Members of this community, which still practices traditional farming, determine soil fertility by observing a variety of rattan and other plants, including those from the families Zingiberaceae and Euphorbiaceae, and employ Myrtaceae as an indicator of soil infertility (Siahaya et al, 2016). These indicators are used to plan rotational fallow periods.…”
Section: Ecosystem Services (Es) Perceptions By Local Communitiesmentioning
confidence: 99%